Utilização do AutoCAD como pré-processador gráfico de sistemas de análise de estruturas - Souza Filho, Romir Soares de (1992)
The fast advance in computer technology (both in hardware and software) has facilitated the development of structural analysis systems that are able to analyse more complex models. The graphic capabilities of a system is one of the most important factores to qualify it, however the development of a specific graphic program need expensive investments and a time consuming. A quick and efficient procedure, with low costs, is the use of general grafic systems, adapted to be a pre-processor and/or post-processor. So, the time saved can be better used on the development and improvement of the structural analysis system. Therefore, it was decided to use AutoCAD to develop a graphic interface to be used as pre-processor of the SALT System. In this work, it is shown how the AutoCAD can be linked to other programs. It is pointed out the importance of neutral exchanged files and presented the AutoSALT, which is the developed graphic pre-processor for the SALT System.